Local probing of Li+ diffusion and concentration in Li-ion battery materials by scanning probe microscopy - Luchkin, Sergey Yurevich (2015)
This thesis presents the results of Scanning Probe Microscopy (SPM) study of Li-ion battery active materials. The measurements have been performed on LiMn2O4 cathodes and graphite anodes extracted from commercial Li batteries at different states of charge and health. The study has been focused on measurements of Li spatial distribution and transport properties in the active electrode materials. Special attention has been paid to influence of fatigue caused by high C rate cycling on Li spatial distribution and local diffusion coefficient. Electrochemical Strain Microscopy (ESM) has been used to access Li transport properties at the nanoscale in LiMn2O4 cathodes. Kelvin Probe Force Microscopy (KPFM) has been used to examine Li spatial distribution in graphite anodes. ESM has been implemented and used in a single frequency mode out of the contact resonance for the first time. Signal-to-noise ratio analysis has been performed for a number of single- and multi-frequency modes used in ESM. The analysis allowed to establish criteria for a proper cantilever choice and an experimental setup for the optimized detection of surface displacements via lock-in amplifier. Transport properties of Li+ mobile ions in fresh and fatigued LiMn2O4 battery cathodes have been studied at the nanoscale via ESM using time-and voltage spectroscopies. Both Vegard and non-Vegard contributions to ESM signal have been identified in electrochemical hysteresis loops obtained on the fresh and fatigued samples. In fresh cathodes the Vegard contribution dominates the signal, while in fatigued samples different shape of hysteresis loops indicates additional contributions. Non-uniform spatial distribution of the electrochemical loop opening in LiMn2O4 particles studied in the fatigued samples indicates stronger variation of Li diffusion coefficients in fatigued samples’ as compared to the fresh one. Time spectroscopy measurements have revealed suppressed local Li diffusivity in fatigued samples by more than two orders of magnitude as compared to the fresh one. We attributed such reduction of the diffusion coefficient to the accumulation of point defects induced by high C-rate cycling and accompanied structural instability. This mechanism can be specifically important for high C-rate cycling. Li spatial distribution in fresh and fatigued graphite cathodes has been accessed via KPFM using a 2-pass amplitude modulation mode. Core-shell and mosaic surface potential structures have been observed on the fatigued and fresh anodes, respectively. The observed surface potential distributions have been attributed to the apparent Li concentration profiles in graphite. The core-shell potential distribution has been attributed to the remnant Li ions stacked in graphite particles causing irreversible capacity loss. The mosaic potential distribution has been attributed to inactive Li inside graphite at the starting stage of cycling. The results corroborate the “radial” model used to explain the specific capacity fading mechanism at high C rate cycling in Li-ion batteries.